Analysis of Aerodynamic Heating Modes in Thermochemical Nonequilibrium Flow for Hypersonic Reentry - Shuai He; Wei Zhao; Xinyue Dong; Zhuzhu Zhang; Jingying Wang; Xinglian Yang; Shiyue Zhang; Jiaao Hao; Ke Sun (Energies, 2025)
Thermochemical nonequilibrium significantly affects the accurate simulation of the aerothermal environment surrounding a hypersonic reentry vehicle entering Earth’s atmosphere during deep space exploration missions. The different heat transfer modes corresponding to each internal energy mode and chemical diffusion have not been sufficiently analyzed. The existing dimensionless correlations for stagnation point aerodynamic heating do not account for thermochemical nonequilibrium effects. This study employs an in-house high-fidelity solver PHAROS (Parallel Hypersonic Aerothermodynamics and Radiation Optimized Solver) to simulate the hypersonic thermochemical nonequilibrium flows over a standard sphere under both super-catalytic and non-catalytic wall conditions. The total stagnation point heat flux and different heating modes, including the translational–rotational, vibrational–electronic, and chemical diffusion heat transfers, are all identified and analyzed. Stagnation point aerodynamic heating correlations have been modified to account for the thermochemical nonequilibrium effects. The results further reveal that translational–rotational and chemical diffusion heat transfers dominate the total aerodynamic heating, while vibrational–electronic heat transfer contributes only about 5%. This study contributes to the understanding of aerodynamic heating principles and thermal protection designs for future hypersonic reentry vehicles.